Seasonal Variation on The Prevalence of Ectoparasites in Rodents in Kilombero District, Tanzania - Amani Juma; Abdul Katakweba; Julius Medardus (Journal of Applied Veterinary Science And Technology, 2026)
Background: Significant health risks to humans and livestock are posed by rodents, which act as synanthropic pests damaging crops and food while harboring blood-feeding ectoparasites. These ectoparasites function as critical vectors for various zoonotic diseases. Purpose: Investigation was undertaken to determine the diversity, prevalence, and seasonal variation of rodent ectoparasites in the Kilombero district to elucidate their role in disease transmission. Method: A cross-sectional study was conducted in the Kilombero District between November 2022 and February 2023. Trapping of rodents was performed across human residences, peridomestic areas, and crop vegetation. Following anesthesia with diethyl ether, ectoparasite collection was executed, with subsequent identification based on standard taxonomic keys. Results: Peak prevalence of rodents was observed during the wet season (64.1%) compared to the dry season (35.9%). Mastomys natalensis was identified as the predominant species (57.4%) during the wet season, with nearly 40% captured within crop vegetation. Of the 387 rodents captured, a male predominance of 58.9% was recorded, while females comprised 41.1%. Specifically, male Mastomys natalensis constituted 51.9% (201/387) of the total catch, whereas male Rattus rattus accounted for 6.7% (26/387). Recovery of 1,803 ectoparasites was achieved, with Laelaps spp. (90.3%) identified as the most prevalent, followed by Xenopsylla brasiliensis (7.4%), Haemaphysalis spp. (1.2%), and Echidnophaga gallinacea (1.1%). During the wet season, infestation with Laelaps spp. was found in 183 (73.8%) of the 248 captured rodents, with Mastomys natalensis harboring 90% of the mites. In the dry season, 301 ectoparasites were recovered, of which approximately three-quarters were Laelaps spp. (75.4%), primarily sourced from Mastomys natalensis (88.4%). Conclusion: Enhanced management of rodent ectoparasites and increased community awareness regarding their presence are recommended to mitigate the potential transmission of zoonotic diseases.